Improving Student Learning Motivation with Peer Tutor Learning Method - Nida’Ul Husna; Puji Destiani; Kun Hisnan Hajron (Prosiding University Research Colloquium, 2021)
The purpose of this study was to increase the effect of using peer tutoring methods as ameans of increasing student learning motivation at SD Negeri Gulon 1 in the Covid-19pandemic era. Based on the results of data analysis in the first cycle with an average of88.67 before the treatment, while in the second cycle there was an average increase of100 after the treatment, namely peer tutors. So it can be concluded that using peertutoring methods can increase student learning motivation.